Verdict on The Shroud: Evidence for The Death and Resurrection of Jesus Christ - Kenneth E. Stevenson; Gary R. Habermas (Michigan Servant Books, 1981)
Verdict on the shroud. Ann Arbor, Mich. : Servant Books, c1981 . [16] p. of plates
I. Facts about the shroud. The phenomenon of the shroud.The shroud and history. The man buried in the shroud. The New Testament and the shroud. Science and the shroud: pre-1978. Science and the shroud: post-1978 -- II. Conclusions from the facts. Fraud and the shroud. The authenticity of the shroud. Is it Jesus? -- III. The significance of the shroud. The death of Jesus: new insights? The resurrection of Jesus: new evidence? The naturalism-supernaturalism debate. Conclusion: Jesus' burial shroud.
Keywords: Christian Antiquities (3GdBKGQ GdeSjMjIs; Holy Shroud